Zonas de compensação - Leote, Rosangela da Silva [UNESP]; Carvalho, Miguel Alonso Araujo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Extension project "Com-compensation zones" is in its fourth year of development and aims to design and conduct an art exhibit, based on experiments and application of theoretical concepts provided in workshops during the year 2015. This process enables workshop participants to create the execution of works in collaboration, these works will be exhibited in April, in the year 2016. This project has a long history, which began in 2001 but implemented in 2012, having been awarded with the support of PROEX, including monitoring of grants and funding. In this work are addressed aesthetic issues and creating processes with the objective of the assembly planning an art exhibit that uses interactive technologies in its design. The operating methodology seeks to relate concepts about art, in addition to proposing an interdisciplinary perspective. For this goal, we intend to contextualize the artistic processes relating them to the concept of "technological aesthetic." In the mentioned exhibition, the works have formal aspects which aims to make manifest effects of the conceptual basis of devel-saving research addressing the convergence between Art, Science and Technology. In short, this proposal is dedicated to developing and applying methods of creation, in addition to addressing other concepts involved, or arising in the development of an exhibition called "compensation zones".

O projeto de Extensão “Zonas de Compensação” no seu quarto ano de desenvolvimento, visa projetar e realizar uma exposição artística baseada em experimentos e aplicação de conceitos teóricos fornecidos em workshops no decorrer do ano de 2015. O processo possibilita aos participantes, das oficinas de criação, à realização de obras em colaboração, que serão expostas em abril, no ano de 2016. Este projeto tem uma longa trajetória, iniciado em 2001, mas implementado em 2012, tendo sido contemplado com o apoio da PROEX, incluindo bolsas de monitoria e verba. Nesse trabalho são abordadas questões estéticas e processos de criação tendo como mote o planejamento da montagem de uma exposição artística que utiliza tecnologias interativas em sua concepção. Seu formato busca relacionar conceitos sobre arte, mas também propõe uma perspectiva interdisciplinar. Para tal objetivo, pretende-se contextualizar os processos artísticos relacionando-os ao conceito de “estéticas tecnológicas”. Na exposição citada, as obras têm aspectos formais onde se pretende fazer manifestar os ecos da base conceitual das pesquisas desenvolvidas no contexto da convergência entre Arte, Ci- ência e Tecnologia. Em suma, esta proposta se dedica a desenvolver e aplicar métodos de criação além de abordar outros conceitos envolvidos, ou surgidos, no desenvolvimento de uma exposição chamada “Zonas de compensação”.
Keywords: Art technology; Perception; Creative process; Arte tecnologia; Percepção; Processo criativo